PRESENCE OF EVIDENCE OF MEDICAL RECORD CONTENTS IN TRIALS FOR CRIMINAL ACTIONS OF MALPRACTICE BASED ON MINISTER OF HEALTH REGULATIONS NUMBER 269/MENKES/PER/2008 JUNCTO LAW NUMBER 8 OF 1981 CONCERNING THE BOOK OF CRIMINAL PROCEDURES - David Mallisa Allorante; Margo Hadi Pura (Jurnal Ilmiah Advokasi, 2024)
Victimology, from the words victim (victim) and logic (science), Latin victim (victim) and logos (science). In simple terms, victimology means the science of victims (crimes). According to the Crime Dictionary dictionary quoted by an Abussalam expert, victims are "people who have suffered physical or mental suffering, lost objects or resulted in death for acts or attempts of minor violations committed by perpetrators of criminal acts and others". Here it is clear what is meant by "people who experience physical suffering and so on" are victims of violations or criminal acts.In conducting research so that it is carried out optimally, the researcher uses several methods. In this study, the normative juridical approach is used. Normative juridical namely the study of legal principles, legal systematics, level of legal synchronization and legal comparison. This normative juridical is an effort to inventory positive law. This approach examines legal issues based on normative rules whether they are compatible with social life. To obtain the data and information referred to by this thesis, the authors use the nature of descriptive analysis research.The crime of theft is an act of crime, which greatly disturbs the comfort of the people. For that we need a consistent action that can uphold the law, so that harmony is established. As it is known that Law Number 8 of 1981 Concerning Criminal Procedure Law adheres to a criminal justice system that prioritizes the protection of human rights, but if the provisions regarding this matter are considered in more depth, it turns out that only the rights of submission/defendant are much highlighted while the rights of victims of theft. In line with this principle, the public, especially the mass media, focuses more on the rights of the suspect/defendant rather than making an issue of the Protection of Victims of Theft.Keywords: Victimology, Theft Crime, Criminal Justice System